Identifikasi Peresepan Obat Berpotensi Tidak Tepat pada Pasien Geriatri Rawat Jalan Diabetes Mellitus Tipe 2 di RS Bhakti Wira Tamtama Semarang - Hanung, Hanung Puspita Adityas; Sulistyorini, Sri; Indah, Putri (Sultan Agung Islamic University of Semarang, 2025)
Background: As the geriatric population in Indonesia increases, it is estimated that the number of diabetes mellitus sufferers will continue to increase. One of the problems that geriatric patients with diabetes mellitus often encounter is Medications That May Be Inappropriate (PIMs), this can result in various undesirable effects and the most fatal, even death. This study aims to identify potentially inappropriate medications in geriatric outpatients with Type 2 Diabetes Mellitus using the Beers criteria at the Bhakti Wira Tamtama Hospital, Semarang. Method: This research is an observational study using a descriptive research design conducted retrospectively using medical record instruments and the Beers Criteria 2023. The research subjects who met the inclusion and exclusion criteria were 100 patients. Results: The results of the study showed that the majority of patients were female (65%), had an age range of 60-74 years (94%), received a total of ≥5 types of medication (68%), and the most common comorbidity was hypertension (30,18%). The percentage of PIMs events was 221 (42.58%) events. Drugs included in category 1 were 178 (80.54%), category 2 were 12 (5.43%), category 3 were 9 (4.07%), category 4 were 3 (1.36%), and category 5 as many as 19 (8.60%). Conclusion: Outpatient geriatric patients with Diabetes Mellitus Type 2 at Bhakti Wira Tamtama Hospital Semarang experienced 221 (42.58%) PIMs with the highest percentage of medication being glimepiride with 49 (21.30%) incidents